QoS Based Approach for Web Service Recommendation (International Journal of Engineering and Computer Science, 2016)
Web services are important integrated software components for the support of interoperable machine to machine communication over internet. Web services have been widely used for building services oriented applications in industry in recent years. On internet publically available web services are widely increased in recent years. For the web services users it is very hard to select a proper web services among a large amount of services available on internet. Improper selection of web services may cause many problems (e.g., ill-suited performance) to the resulting applications. In this paper we proposed Collaborative Filtering (CF), we propose an innovative CF algorithm for Q-o-S-based web service recommendation. we provide a personalized map for browsing the recommendation results. The map explicitly shows the QoS relationships of the recommended web services as well as the basic structure of the QoS space by using map metaphor such as dots, areas, and spatial arrangement.